Behavioral and Neural Valuation of Foods Is Driven by Implicit Knowledge of Caloric Content. (December 2014) - Tang, Deborah W.; Fellows, Lesley K.; Dagher, Alain
The factors that affect food choices are critical to understanding obesity. In the present study, healthy participants were shown pictures of foods to determine the impact of caloric content on food choice. Brain activity was then measured while participants bid for a chance to purchase and eat one item. True caloric density, but not individual estimates of calorie content, predicted how much participants were willing to pay for each item. Caloric density also correlated with the neural response to food pictures in the ventromedial prefrontal cortex, a brain area that encodes the value of stimuli and predicts immediate consumption. That same region exhibited functional connectivity with an appetitive brain network, and this connectivity was modulated by willingness to pay. Despite the fact that participants were poor at explicitly judging caloric content, their willingness to pay and brain activity both correlated with actual caloric density. This suggests that the reward value of a familiar food is dependent on implicit knowledge of its caloric content.